(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
Disability Studies has adopted new dimensions, approaches and theories in its exploration of disablement in literature, culture and society; still, it has vast trajectories of discourse that need greater academic attention. People with disability around the world experience deep roots of stigmatisation, negative metaphors, discriminatory languages and stereotypes. Translation facilitates questioning of such linguistic and socio-cultural reprehensions that undermine the subjectivities of people with disabilities. The intersection of disability studies and translation studies is an emerging discipline, however, the first research article in this area dates back to a publication in 1997, “Disability Issues in Translation/Interpretation” by J.F. Smart and D.W. Smart, which deal with translation, interpretation and cultural differences in disability. Several research works are available in the context of audio-visual translation – subtitling/captioning for the deaf and audio description for the blind. Pérez-González’s The Routledge Handbook of Audiovisual Translation (2019) is a notable work in this area. C.B. Roy and J. Napier’s edited book, The Sign Language Interpreting Studies Reader (2017), suggests that language interpretation is another area closely related to disability and translation.